Vitamin D Receptor Gene Polymorphism and Vitamin D Plasma Concentration: Correlation with Susceptibility to Tuberculosis - Jalil Rashedi; Mohammad Asgharzadeh; Seyyed Reza Moaddab; Leyla Sahebi; Majid Khalili; Mohammad Mazani; Jalal Abdolalizadeh (Tabriz University of Medical Sciences, 2014)
Purpose: It is estimated that one third of the world's population were infected with M. tuberculosis, but only 10% of them have developed in to disease form. This subject refers to differences in host immune system activity against the tuberculosis. Vitamin D and its receptor (VDR) are important factors in the host innate immune system against the tuberculosis. In the present study VDR gene polymorphisms and its relationship with plasma vitamin D levels in susceptibility to tuberculosis have been investigated. Methods: The subjects were 84 patients with tuberculosis and 90 healthy controls. Vitamin D levels were measured in all study participants. DNA was isolated from the blood leukocytes of all groups and amplified by polymerase chain reaction (PCR). Then restriction fragment length polymorphism (RFLP) was performed on each PCR products to study the VDR gene polymorphisms. The statistical analyses were conducted using SPSS. Results: There was no statistically significant relationship between polymorphisms of FokI, BsmI, ApaI and TaqI in VDR gene and susceptibility to tuberculosis. Vitamin D deficiency and susceptibility to tuberculosis were closely related (95% CI -0.08 - 4.7, P = 0.059). Also the relationship between plasma vitamin D levels and frequency of FokI-ff gene polymorphism was significant in all study participants (P = 0.045). Conclusion: When the genotype frequencies of VDR gene polymorphisms were analyzed with respect to plasma vitamin D levels, a significant association was seen. As an enhancement in plasma vitamin D levels in individuals (with FokI-ff genotype and low levels of vitamin D) may protect them against active tuberculosis.